Evaluating the effect of cost related factors on relationship quality: An investigation of retailer-supplier relationship in Bangladesh - Tareque Aziz, Mohammed (© 2013, Emerald Group Publishing Limited, 2016)
This article was published in the International Journal of Retail & Distribution Management [© 2013, Emerald Group Publishing Limited.] and the definite version is available at : http://dx.doi.org/10.1108/IJRDM-05-2013-0098 The Journal's website is at: http://www.emeraldinsight.com/doi/full/10.1108/IJRDM-05-2013-0098